Economic keystones: the weight system of the Kingdom of Judah - Ḳlẹter, Raz (Journal for the study of the Old Testament / Supplement series, 1998)
This book presents a full picture of the weight system of Iron Age Judah, based on archaeological finds, historical sources and biblical texts. This book offers a complete picture of the weight system of Iron Age Judah, involving a careful study of the typology, date, context, weight standards, inscription and function of hundreds of weights (with a full catalogue). As against the common view, the author suggests that all the weights belong to one system based on one basic sheqel standard. The weights are mostly not 'royal weights' and have nothing to do with Josiah's reform. The 'sheqel of the sanctuary' was never used in practice in First-Temple Judah. The study leads to new insights about the relation of the Judaean system to other weight systems, as well as about international trade and the economy of the Kingdom of Judah.